Embracing the family member the person in psychic suffering in nursing studies - Cristiene Barbosa Lima; Mércia Zeviani Brêda; Maria Cícera dos Santos de Albuquerque (Universidade de Fortaleza, 2014)
Objective: To evidence knowledge published in the field of nursing care on the embracement to family members of people in psychic suffering in health services. Methods: Integrative review, accomplished in June and July 2012, in LILACS, BDENF, IBECS, MEDLINE and SciELO databases, using the keywords: "mental health", "user embracement" and "family". The inclusion criteria were met by 14 texts, written by professionals and nursing students, in Portuguese language, published between 2007 and 2011. The data was resumed in four tables and a figure, and analyzed under the framework of the user embracement by the National Humanization Policy. Results: No trends related to studies on user embracement can be stated. Most publications adopt a qualitative approach and content analysis, with evidence being type III. There is a predominance of research having health professionals as subjects. However, the family and other actors are starting to get involved. Taking similar care of the family and the person in suffering is highlighted in all of the studies analyzed. It was evidenced need for interaction between the health services and the specialized mental health network and for training the team in order to minimize to the difficulties faced by the family. Conclusion: Family embracement was often pointed as a device that facilitates the rehabilitation. There is much to be done toward its embracement in health services, so that the family is allowed to realize that their living is not necessarily the continuity of the trouble faced by the other person. doi:http://dx.doi.org/10.5020/18061230.2013.p571